Two Worlds, One Identity: Postcolonial Reading of Space in Sherman Alexie's The Absolutely True Diary of a Part-Time Indian - Angelique Sheva Kurniawan; Zuhrul Anam (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how the reservation shape’s identity in Sherman Alexie’s The Absolutely True Diary of a Part-Time Indian (2007). Rather than treating the setting as a passive background, this paper contributes to postcolonial spatial studies by showing how the reservation actively constructs identity before any physical movement takes place. This qualitative study applies Sara Upstone’s concepts of "place" and "space" to analyze the novel's dialogues, narratives, and events. This specific framework reveals how colonial structures turn the reservation into a fixed "place" of poverty and isolation that Junior internalizes. However, the analysis demonstrates that Junior’s relocation to Reardan transforms this restrictive environment into a flexible "space" for self-definition. In conclusion, the study argues that the reservation is not permanently limiting, but can be transformed into a dynamic environment through individual agency and resistance.